The interest of Bavarian primary school pupils in geographical topics and methods – selected results of an empirical survey. Issue 5 (3rd September 2017) - Lorenz, Aline; Roth, Anna; Priese, Carolin; Peukert, Eva; Mertel, Stefanie; Bloß, Susanne; Mehren, Rainer
ABSTRACT: Interest is a central learning prerequisite for teaching. The article deals with a survey among 1600 primary school pupils in forms 2, 3 and 4 (ages 7–10) in the German federal state of Bavaria who were interviewed on their interest in geographical topics and working methods. They were given a questionnaire including 40 items to indicate their individual interest on a five-point Likert scale. The results show that the subscale 'natural disaster' generates the highest interest, followed by 'phenomena of geoscience' and 'people and peoples'. The interest in all three subscales decreases with increasing age. Furthermore, several gender-specific differences occur. Among the working methods, experimenting, films and computers hold the first three places whilst again showing significant differences concerning age group as well as gender.